How Price Perception and Digital Marketing Drive Frozen Food Consumers' Repurchase Intention: The Role of Purchasing Decision Mediation - yeni mauliana; Adnan; Ikramuddin (Institut Agama Islam Negeri Lhokseumawe, 2026)
This study aims to examine the influence of price perception and digital marketing on repurchase intention and also explores the role of purchase decisions as an intervening variable in this relationship. This study uses primary data collected by distributing questionnaires as the main instrument, with the Hair method applied for sampling. The study consists of a total sample size of 144 respondents. This study uses a quantitative approach using Structural Equation Modeling (SEM). The findings reveal that digital marketing and price perception positively affect purchase decisions. Furthermore, purchase decisions and digital marketing positively and significantly influence repurchase intention. However, price perception, on its own, does not have a significant effect on repurchase intention. Also, the purchase decision partially mediates the relationship between price perception and digital marketing with repurchase intention. It implies that the purchase decision variable serves as a key intermediary in the impact of price perception and digital marketing on repurchase intention for frozen food products in Lhokseumawe City. Substantially, price perception itself does not significantly affect repurchase intention when not mediated by purchase decisions.